Slipped-strand DNAs formed by long (CAG)·(CTG) repeats: slipped-out repeats and slip-out junctions - Pearson, Christopher E. (Oxford University Press, 2002)
The disease-associated expansion of (CTG)·(CAG) repeats is likely to involve slipped-strand DNAs. There are two types of slipped DNAs (S-DNAs): slipped homoduplex S-DNAs are formed between two strands having the same number of repeats; and heteroduplex slipped intermediates (SI-DNAs) are formed between two strands having different numbers of repeats. We present the first characterization of S-DNAs formed by disease-relevant lengths of (CTG)·(CAG) repeats which contained all predicted components including slipped-out repeats and slip-out junctions, where two arms of the three-way junction were composed of complementary paired repeats. In S-DNAs multiple short slip-outs of CTG or CAG repeats occurred throughout the repeat tract. Strikingly, in SI-DNAs most of the excess repeats slipped-out at preferred locations along the fully base-paired Watson–Crick duplex, forming defined three-way slip-out junctions. Unexpectedly, slipped-out CAG and slipped-out CTG repeats were predominantly in the random-coil and hairpin conformations, respectively. Both the junctions and the slip-outs could be recognized by DNA metabolizing proteins: only the strand with the excess repeats was hypersensitive to cleavage by the junction-specific T7 endonuclease I, while slipped-out CAG was preferentially bound by single-strand binding protein. An excellent correlation was observed for the size of the slip-outs in S-DNAs and SI-DNAs with the size of the tract length changes observed in quiescent and proliferating tissues of affected patients—suggesting that S-DNAs and SI-DNAs are mutagenic intermediates in those tissues, occurring during error-prone DNA metabolism and replication fork errors.